2021
DOI: 10.3389/fmicb.2021.745766
|View full text |Cite
|
Sign up to set email alerts
|

The Biocontrol and Plant Growth-Promoting Properties of Streptomyces alfalfae XN-04 Revealed by Functional and Genomic Analysis

Abstract: Fusarium wilt of cotton, caused by the pathogenic fungal Fusarium oxysporum f. sp. vasinfectum (Fov), is a devastating disease of cotton, dramatically affecting cotton production and quality. With the increase of pathogen resistance, controlling Fusarium wilt disease has become a significant challenge. Biocontrol agents (BCAs) can be used as an additional solution to traditional crop breeding and chemical control. In this study, an actinomycete with high inhibitory activity against Fov was isolated from rhizos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 62 publications
0
23
0
Order By: Relevance
“…1S1 ethyl acetate extract accountable for this strain's antibacterial activity was also found by GC‒MS analysis [ 81 ]. Compound ( 3 ) was also detected in the MeOH extract of Streptomyces alfalfae XN-04 with plant growth-promoting and antifungal properties [ 82 ]. Furthermore, compound ( 5 ) was identified in GC‒MS analysis for Streptomyces anulatus NEAE-94 with antibiotics against MDR S. aureus [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…1S1 ethyl acetate extract accountable for this strain's antibacterial activity was also found by GC‒MS analysis [ 81 ]. Compound ( 3 ) was also detected in the MeOH extract of Streptomyces alfalfae XN-04 with plant growth-promoting and antifungal properties [ 82 ]. Furthermore, compound ( 5 ) was identified in GC‒MS analysis for Streptomyces anulatus NEAE-94 with antibiotics against MDR S. aureus [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…alfalfae strain XN-04, Streptomyces sp. NEAU-S7GS2, and St. chartreusis strain WZS021, have root growth-promoting activities on cotton, soyabean and sugarcane, respectively, and genes related to IAA, siderophores, phosphate solubilization were identified in their genomes ( Wang et al, 2018b , Liu et al, 2019, Chen et al, 2021 ). In various studies, IAA has been shown to increase plant root size and distribution, as well as root hairs, resulting in higher nutrient uptake from the soil ( Datta and Basu, 2000 ; Gumiere et al, 2014 ; Liao et al, 2017 ; Ulrich et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Streptomyces albidoflavus St-220 have both biological control activity and plant growth-promoting activity Some Streptomyces strains could significantly improve the biocontrol of Fusarium root rot disease and promote the growth of plant seedlings (El-Tarabily et al, 2009;Goudjal et al, 2016;Tamreihao et al, 2016;Chen et al, 2021). They were generally identified by three properties: IAA production, the abilities to solubilize phosphate and fix nitrogen, and siderophores production (Vurukonda et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, anthropogenic activities to overcome food and space scarcity have negatively influenced the natural environment. Consequently, numerous environmental problems can be witnessed globally, including pollution, global warming, limited availability of water, and the greenhouse effect [1]. Plants, the primary producers in food chains, are most significantly affected by changing environments and become more susceptible to various diseases under environmental stresses.…”
Section: Introductionmentioning
confidence: 99%